2012
DOI: 10.1016/j.febslet.2012.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of Arabidopsis chloroplasts reveals involvement of the STN7 kinase in phosphorylation of nucleoid protein pTAC16

Abstract: a b s t r a c tLight-regulated protein kinases STN7 and STN8 phosphorylate thylakoid membrane proteins and also affect expression of several chloroplast proteins via yet unknown mechanisms. Comparative phosphoproteomics of acetic acid protein extracts of chloroplasts from Arabidopsis thaliana wild type, stn7, stn8 and stn7stn8 mutants yielded two previously unknown findings: (i) neither STN7 nor STN8 kinase was required for phosphorylation of Ser-48 in Lhcb1.1-1.3 proteins; and (ii) phosphorylation of Thr-451 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
4
40
0
Order By: Relevance
“…This finding suggests possible linkages from ethylene signaling to light harvesting. Among those CTR1 kinase-up-regulated and chloroplast-located phosphopeptides, it has been reported that phosphorylation of the T451 amino acid of PTAC16 and the S48 amino acid of LHCB1.1-1.3 (S47 of LHCB1.4 or S46 of LHCB1.5) are STN7-dependent and -independent, respectively (85). Thus, it is likely that there is more than one pathway from CTR1 kinase to chloroplast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests possible linkages from ethylene signaling to light harvesting. Among those CTR1 kinase-up-regulated and chloroplast-located phosphopeptides, it has been reported that phosphorylation of the T451 amino acid of PTAC16 and the S48 amino acid of LHCB1.1-1.3 (S47 of LHCB1.4 or S46 of LHCB1.5) are STN7-dependent and -independent, respectively (85). Thus, it is likely that there is more than one pathway from CTR1 kinase to chloroplast.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast STN7 kinase, which is required for state transitions between photosystem I and photosystem II and for light adaptation, is one of the two light-regulated protein kinases (86). However, neither STN7 nor STN8 (the other light-regulated protein kinase in Arabidopsis) is required for the phosphorylation of S48, S47, or S46 on light harvesting chlorophyll A/B binding proteins 1.1-1.5 (LHCB1.1-1.5, AT1G29920/AT1G29910/AT1G29930/AT2G34430/AT2G34420) (85). Taken together, these data suggest that it is possible that the physical presence of wild-type CTR1 kinase may be required for the up-regulation of PTAC16, STN7, and LHCB protein phosphorylation upon ethylene induction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant TCP34 protein showed specific binding to chloroplast DNA isolated from spinach (Weber et al 2006). Very recently, it was postulated that next to MFP1 and TCP34 also the pTAC16 protein could anchor DNA to the thylakoid membranes (Ingelsson and Vener 2012;Majeran et al 2012). …”
Section: Mfp1 Tcp34 and Ptac16mentioning
confidence: 99%
“…In Arabidopsis, the thylakoid Ser/Thr protein kinase 7 (STN7) and STN8 kinases are light regulated and participate in phosphorylation of thylakoid membrane proteins and stroma proteins. Ingelsson and Vener (2012) performed a thylakoid phosphoproteomics study using Arabidopsis wild-type and the STN mutants stn7, stn8 , and stn7stn8 . The results showed that STN7 is required for the phosphorylation of pTAC16 at the Thr451, and pTAC16 was found to be distributed between thylakoids and nucleoid.…”
Section: Applications Of Phosphoproteomics In Plant Biology Researchmentioning
confidence: 99%